TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7948836 ZenodoArchiveConcept: 7948835 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7948836 10.53832/edtechhub.0166 2339240:N4CC2DD8 2405685:FICAJDR3 2405685:HUR5C9QN 2405685:XVCIV366
Keywords: _r:AddedByZotZen

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7373033 ZenodoArchiveConcept: 7373032 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7373033 10.53832/edtechhub.0144 2405685:499UU2BN 2405685:D7VXZW6I
Keywords: _r:AddedByZotZen

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6817992 10.53832/edtechhub.0171 2405685:KAAC2B78
Keywords: _r:AddedByZotZen

Uzoefu wa Walimu katika kufundisha kwa kutumia teknolojia nchini Tanzania Mapendekezo Juu ya Sera na Utekelezaji - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2023)
This is a Swahili version of the policy brief Teachers’ Experiences of Teaching With Technology in Tanzania: Recommendations for policy and practice published in October 2022. Muhtasari huu wa masuala ya kisera unatoa ripoti ya utafiti wa walimu nchini Tanzania (Julai-Novemba 2021) ambao EdTech Hub iliagiza HakiElimu kuufanya ili kuchangia taarifa itakayosaidia mchakato endelevu wa serikali kuleta mageuzi ya MEWAKA katika ngazi za shule na vituo vya walimu. Dodoso zilichukuliwa kutoka katika uchunguzi wa kihistoria wa kimataifa uliohusisha takriban walimu 20,000+ , kuhusu uzoefu na changamoto zao katika ufikiaji na matumizi ya EdTech, ufundishaji na ujifunzaji, na maendeleo ya kitaaluma katika mwaka 2021, iliyoripotiwa na timu kutoka T4 Education na EdTech Hub. Maneno muhimu: teknolojia ya elimu; matokeo ya kujifunza; mahitaji ya mwalimu; mafunzo endelevu ya taaluma ya ualimu; sauti ya mwalimu / Kauli ya mwalimu; ufikiaji wa teknolojia An output of the EdTech Hub, https://edtechhub.org
DOI 10.53832/edtechhub.0147 ZenodoArchiveID: 7652491 ZenodoArchiveConcept: 7652490 2405685:ECXPS38I KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8363989 10.53832/edtechhub.0174 2405685:ECXPS38I 2405685:MDC3E34G
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7966434 ZenodoArchiveConcept: 7966433 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7966434 10.53832/edtechhub.0168 2405685:CQ8JNCH8
Keywords: _r:AddedByZotZen

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
oldDOI: 10.5281/zenodo.6498098 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 10.5281/zenodo.7716253 10.53832/edtechhub.0082 10.53832/edtechhub.0170 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP 2405685:UJWVTSCK
Keywords: _r:AddedByZotZen

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521062 ZenodoArchiveConcept: 7521061 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521062 10.53832/edtechhub.0145 2405685:M3D6NGR4 2405685:WVRHTVIZ 2486141:V94NMZIU
Keywords: _r:AddedByZotZen

How can messaging apps, WhatsApp and SMS be used to support learning? A scoping review - Jordan, Katy (Technology, Pedagogy and Education, 2023)
In response to disruption to education during the Covid-19 pandemic, mobile phone-based messaging has emerged in some instances as an accessible, low-connectivity way of promoting interactivity. However, no recent reviews have been undertaken in relation to how social media and messaging apps can be used to effectively support education in low- and middle-income countries. In this scoping review, 43 documents were identified for inclusion and three main thematic areas emerged: supporting student learning (including interacting with peers and other students, peer tutoring and collaborative learning; and interacting with teachers, through content delivery, teaching and assessment); teacher professional development (including structured support and prompts, and informal communities of practice); and supporting refugee education. The discussion and findings are both of practical use, to inform responses to the current pandemic and designing initiatives in the future, and will also be useful for advancing research in this expanding field.
Accepted: 2022-05-18T23:30:06Z Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.17863/CAM.84697 2405685:8XW8JR6H

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6980271 ZenodoArchiveConcept: 6980270 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6980271 10.53832/edtechhub.0109 2405685:HPWRQP7M
Keywords: _r:AddedByZotZen

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7781293 ZenodoArchiveConcept: 7781292 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7781293 10.53832/edtechhub.0159 2405685:GS45WQWR
Keywords: _r:AddedByZotZen

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8208265 ZenodoArchiveConcept: 8208264 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8208265 10.53832/edtechhub.0057 10.53832/edtechhub.0173 2405685:47KMRR48 2405685:N2E79MUD
Keywords: _r:AddedByZotZen